Self-Powered and High-Performance Alternating Current Photodetectors to enhance Broadband Photodetection - Singh, Ranveer; Kumar, Mohit; Kim, Unjeong; Seo, Hyungtak (Advanced Electronic Materials, 2022)
Self-powered broadband photodetectors that are easy to fabricate and convenient to operate are highly desirable in numerous optoelectronic applications; however, achieving a fast response time with high sensitivity remains a daunting challenge to their widespread use. In this study, a self-powered, high-performance alternating current photodetector is fabricated by coating plasmonic Au nanoparticles (NPs) onto MoO3. The self-powered photodetector shows high detectivity (≈4.6 × 1010 Jones) and a good responsivity of 3.8 µA W−1, due to the alternating current photovoltaic effect. The photodetector exhibits a rapid response with the rise and fall times of 35 and 48 ms, respectively, under self-biased conditions. Conductive atomic force microscopy demonstrates nanoscale charge transport and current generation, suggesting the possibility of fabricating a sub-nanometer (≈50 nm) sized photodetector. Results thus observed are attributed to the relative shift and realignment between quasi-Fermi levels under non-equilibrium conditions, caused by inhomogeneous charge carrier generation. The results presented in this study introduce a simple approach to enhance self-powered broadband photodetection while enabling high-performance for advanced optoelectronic applications in the future; these applications include smart security, optical communication, digital display, and sensing, amongst others.
Keywords: AC photovoltaic; Alternating current; Broadband photodetector; High-performing; Nano scale; Optoelectronic applications; Performance; Photo detection; Photovoltaics; Self-powered; AC photovoltaic; broadband photodetectors; high-performing; nanoscale; self-powered